Faktor-Faktor yang Mempengaruhi Kesadaran Mengenai Pembayaran Pajak Kendaraan Bermotor - Putri Oktatia Harum; Tutut Dewi Astuti (Income Journal: Accounting, Management and Economic Research, 2024)
As one of the largest sources of income for the country, tax arrears are a problem that must be considered. One of the taxes that experiences an increase in arrears every year is motor vehicle tax. Motor vehicle taxes administered by regional governments result in reduced regional income and affect regional operational activities. Therefore, it is necessary to know the factors that trigger delinquency in motor vehicle tax payments. This research aims to determine the influence of tax knowledge, income level, and tax sanctions on awareness of paying motor vehicle taxes. The samples used were 100 samples, taken using the accidental sampling method. The independent variables in the research are tax knowledge, income level, and tax sanctions. Meanwhile, the dependent variable in the research is awareness of paying taxes. The research used descriptive statistical analysis techniques, data quality testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing carried out with SPSS 26 software. The results of the research conducted showed that the variables of tax knowledge and tax sanctions had an effect on awareness of paying motor vehicle taxes . Meanwhile, the income level variable has no effect on awareness of paying motor vehicle tax. The results of the research can provide additional information regarding factors that influence awareness of paying taxes and can help parties who are working on awareness of paying taxes